Discrete Math

posted by .

Use mathematical induction to establish the following formula.

n
Σ i² / [(2i-1)(2i+1)] = n(n+1) / 2(2n+1)
i=1

Thanks for any helpful replies :)

  • Discrete Math -

    check if true for n=1
    LS = 1/(1(3)) = 1/3
    RS = 1(2)/(2(3) = 2/6 = 1/3 , checks!

    Assume it to be true for n = k
    that is ....
    1/(1(3)) + 4/(3(5)) = .... k^2/((2k-1)(2k+1)) = k(k+1)/(2(2k+1))

    prove then it must be true for n = k+1
    that is
    1/(1(3)) + 4/(3(5)) + .. + (k+1)^2/((2k+1)(2k+3)) = (k+1)(k+2)/(2(2k+3))

    LS = k(k+1)/2(2k+1)) + (k+1)^2/((2k+1)(2k+3))

    =[k(k+1)(2k+3) + 2(k+1)^2]/[2(2k+1)(2k+3)]
    = (k+1)[k)2k+3) + 2(k+1)]/[2(2k+1)(2k+3)]
    = (k+1)[2k^2 + 5k + 2]/[2(2k+1)(2k+3)]
    = (k+1)(2k+1)(k+2)/[2(2k+1)(2k+3)]
    = (k+1)(k+2)/(22k+3)
    = RS

    QED!

  • small typo - Discrete Math -

    6th line should have been

    1/(1(3)) + 4/(3(5)) + .... + k^2/((2k-1)(2k+1)) = k(k+1)/(2(2k+1))

  • Discrete Math -

    Ok thank you for your helpful response! I have a couple of questions though. . .

    Is the 15th line suppose to be '(k+1)(k+2)/(22k+3)'?

    Also, the 16th line = RS, which is what exactly?

  • Discrete Math -

    line 15th, clearly a typo, was hoping you would realize it was
    = (k+1)(k+2)/(2(2k+3))

    in 1/(1(3)) + 4/(3(5)) + .. + (k+1)^2/((2k+1)(2k+3)) = (k+1)(k+2)/(2(2k+3))
    there is a left side (LS) and a right side (RS) of the equation.
    I started with LS and proved that it equals the RS, thus showing that the equation is true.

  • Discrete Math -

    Yea that's what I thought. . .Hey if you don't mind helping me further I have been working on this problem for a while and I am a bit stuck. IDK where to go from here or if I am doing it correctly:

    Use mathematical induction to prove the truth of each of the following assertions for all n ≥1.

    5^2n – 2^5n is divisible by 7

    If n = 1, then 5^2(1) - 2^5(1) = -7, which is divisible by 7. For the inductive case, assume k ≥ 1, and the result is true for n = k; that is 7 | (5^2k + 2^5k). Use the assumption to prove n = k + 1, in other words, 5^(2(k + 1)) - 2^(5(k + 1)) is divisible by 7. Now,

    5^(2(k + 1)) - 2^(5(k + 1))
    = 5^(2k + 2) - 2(5k + 5)
    = 5^(2k) · 5^2 - 2^(5k) · 2^5
    = 25 · 5^(2k) - 32 · 2^(5k)
    = IDK what to do from here. . .

    Any suggestions? Thank you again!

  • Discrete Math -

    Any suggestions?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Discrete Math

    Justifying your conclusions (you could also use examples in order to illustrate your results). What can you say about the sets A and B if we know that: 1. A ∪ B = A 2. A ∩ B = A Thanks for any helpful replies :)
  2. Discrete Math

    Use mathematical induction to prove the truth of each of the following assertions for all n ≥1. n³ + 5n is divisible by 6 I really do not understand this to much. This is what I have so far: n = 1, 1³ - 5(1) = 6, which is divisible …
  3. Discrete Math

    Use mathematical induction to prove the truth of each of the following assertions for all n ≥1. 5^2n – 2^5n is divisible by 7 If n = 1, then 5^2(1) - 2^5(1) = -7, which is divisible by 7. For the inductive case, assume k ≥ …
  4. Discrete Math

    Why use mathematical induction to get the sum of a sequence?
  5. Math - Mathematical Induction

    3. Prove by induction that∑_(r=1)^n▒〖r(r+4)=1/6 n(n+1)(2n+13)〗. 5. It is given that u_1=1 and u_(n+1)=3u_n+2n-2 where n is a positive integer. Prove, by induction, that u_n=3^n/2-n+1/2. 14. The rth term of …
  6. Math

    The scores of 10 students on their midterm exam (x) and on their final (y) yielded the following data. Σx = 638 Σx2 = 43,572 Σy = 690 Σy2 = 49,014 Σxy = 44,636
  7. Algebra

    I'm trying ti find the correlation coefficient for the following: The scores of 10 students on their midterm exam (x) and on their final (y) yielded the following data. Σx = 638 Σx2 = 43,572 Σy = 690 Σy2 = 49,014 …
  8. precalculus

    Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) 7 + 13 + 19 + …+[6(k - 1) + 1] + (6k + 1) + [6(k + 1) + 1] 8 + 14 + 20 + …+[7(k - 1) + 1] + (7k + 1) 7 + 13 + 19 + …+(6k + 1) 7 + 13 + 19 + ...+[6(k - 1) + 1] + (6k7 …
  9. precalculus

    Can you check my answers? 1.Which of the following shows the best next step to prove the following by mathematical induction?
  10. Mathematical Induction

    Use mathematical induction to prove that the following is true. 8+11+14...+(3n+5)=1/2n(3n+13), for all n in the set of natural numbers.

More Similar Questions